Nilai Pendidikan Hindu Dalam Aksara Modre Pada Ulap-Ulap Bangunan Suci - I Nyoman Sulastra; I Nyoman Subagia; I Nyoman Temon Astawa (Jayapangus Press, 2026)
This study was prompted by a growing paradigm shift among the younger generation, who tend to reduce the meaning of sacred religious symbols merely to architectural decorative ornaments. It aimed to explore the textual forms, functions, and Hindu educational values embedded within the modre script on the ulap-ulap (sacred cloths) of shrines at Pura Agung Pasek Sumertha, East Denpasar. A qualitative approach was employed, combining exploratory-interpretative, ethnographic, and phenomenological methods, with data gathered via participant observation, in-depth interviews, literature review, and documentation. The findings present three main results. First, the forms of the modre script are characterized by sacred curved, circular, and spiral lines integrated with traditional Balinese ornaments, creating esoteric calligrams centered on the theological symbols of Omkara and Rwa Bhineda. Second, the script functions as a multi-layered medium fulfilling religious-theological roles as physical manifestations of the divine, protective-purification purposes as spiritual shields against negative energies, aesthetic religious enrichment, and socio-cultural preservation. Third, it contains comprehensive Hindu educational values covering religious (sradha and bhakti), ethical (susila), spiritual, cultural, aesthetic, social (ngayah tradition), and philosophical dimensions that cultivate cosmic-divine awareness. This study concludes that the modre script on ulap-ulap plays a vital role as an educational and cultural medium that effectively instills noble character while safeguarding the religious cultural identity of Bali against modern urban challenges.